Faith-Based Character Education: Solution to Improve the Moral of the Nation - Haryanto Haryanto (Universitas Muhammadiyah Enrekang, 2022)
Various problems faced by the Indonesian nation stem from low character and morals. The formulation of national education goals that focus on national characters has not been fully realized. Among the indicators are the HDI which is still low, the high rate of corruption, rampant intolerance and acts of violence in the name of religion, the emergence of separatist movements that threaten the diversity and integrity of the Unitary State of the Republic of Indonesia, and so on. The rearrangement of character education by placing faith as the essence of the entire educational structure is the main solution in improving the nation's morals, because good individual behavior is based on his own moral awareness in order to realize his devotion to his God and get good rewards from Him